Students leadership development through Tangkap Lokam game - Nisa Ariantini; Novi Rosita Rahmawati (Research and Social Study Institute, 2019)
Games, such as the traditional ones, might be benefitted as an alternative media for the delivery of Guidance and Counseling service. With regards to the statement, one of the peculiar games in Indonesia is Tangkap Lokam. Through the conduct of the study, the elements of leadership will be described through the conduct of the Tangkap Lokam games. Then, within the conduct of the study, the qualitative approach using the symbolic interactionism method had been implemented and the study itself took place in the 5th State Junior High School Tarakan. The results of the study show that the construction within the Tangkap Lokam game has implications that might improve the leadership of the students.